2004
DOI: 10.1007/s00256-004-0780-z
|View full text |Cite
|
Sign up to set email alerts
|

End plate marrow changes in the asymptomatic lumbosacral spine: frequency, distribution and correlation with age and degenerative changes

Abstract: End plate marrow signal intensity changes are present in the lumbar spine of some asymptomatic subjects with a characteristic location along the spine and in vertebral end plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 16 publications
9
73
0
4
Order By: Relevance
“…In our study, the carefully selected group of LBP patients with M1 consisted of 24 (2.4%) patients of the 1,015 base population. In previous studies, the reported prevalence of subchondral signal abnormalities varies, that of hypointensities between 4% and 16% [2,6,11,13,17,22]. This is obviously due to varying criteria for abnormalities and selection of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the carefully selected group of LBP patients with M1 consisted of 24 (2.4%) patients of the 1,015 base population. In previous studies, the reported prevalence of subchondral signal abnormalities varies, that of hypointensities between 4% and 16% [2,6,11,13,17,22]. This is obviously due to varying criteria for abnormalities and selection of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Further large-scale studies are required to clarify this issue given the reports of spinal pathoanatomic findings among asymptomatic individuals [8,9,30], including Modic changes [36]. Finally, this study was cross-sectional in design and therefore we neither infer causation between IVD pathology and Modic changes nor comment with certainty regarding the natural history of spinal pathoanatomy across the life course or the pathologic sequence of Modic changes.…”
Section: Discussionmentioning
confidence: 99%
“…In asymptomatic people, MCs have been reported as being mainly small and located in the anterior parts of the vertebrae at the upper lumbar levels [7]; whereas in people with LBP, MCs are larger, located at the lower lumbar levels [19] and more likely to involve more than just the anterior part of the endplate [9]. Although MCs are known to change from one type to another [26], only 23 % of the persons with MCs in a nonclinical population did not have MCs 4 years later [9].…”
Section: Introductionmentioning
confidence: 99%